IFN-α augments natural killer-mediated antibody-dependent cellular cytotoxicity of HIV-1-infected autologous CD4(+) T cells regardless of major histocompatibility complex class 1 downregulation - Tomescu, Costin (AIDS, 2017)
DESIGN: We have previously shown that IFN-α stimulation augments direct natural killer (NK) cell lysis of autologous CD4(+) primary T cells infected with certain HIV-1 isolates based upon major histocompatibility complex class 1 (MHC-1) downregulation capacity. Here, we investigated if antibody-dependent cellular cytotoxicity (ADCC) could trigger lysis of HIV-1 isolates that were resistant to direct NK lysis and if IFN-α prestimulation of NK cells could further enhance ADCC. METHODS: Using broadly neutralizing monoclonal antibodies against gp120 (VRC01 or PGV04) or plasma from HIV-1-infected patients (ART-suppressed or elite controller) to trigger ADCC, we measured NK cell chromium release cytotoxicity against HIV-1-infected autologous CD4(+) primary T cells and NK cell CD107a degranulation against gp120-coated CD4(+) T cells. Total or NK-depleted peripheral blood mononuclear cells were used as effectors in the presence or absence of IFN-α prestimulation. RESULTS: Plasma from HIV-1-infected patients and monoclonal antibodies against gp120 could trigger NK-dependent ADCC lysis of viral isolates that were resistant to direct NK cell lysis following IFN-α stimulation. In contrast, viral isolates that exhibited potent MHC-I downregulation capacity could be lysed by NK cells through either IFN-α stimulated direct cytotoxicity or through ADCC. When utilized in combination, IFN-α prestimulation significantly augmented ADCC lysis of HIV-1-infected target cells and increased NK cell CD107a degranulation against gp120-coated ADCC targets (P <0.05, n =6). CONCLUSION: HIV-1 isolates with lower MHC-I downregulation capacity are resistant to direct lysis following IFN-α stimulation but retain sensitivity to ADCC. IFN-α presti-mulation can significantly increase NK-mediated clearance of HIV-1-infected target cells by both ADCC and/or direct cytotoxicity depending on MHC downregulation status.